The use of the CRB-65 severity of illness score to determine the need for admission of patients with community-acquired pneumonia presenting to an emergency department - Kabundji, Dalton Mulombe (My University, 2012)
Introduction: The decision as to the most appropriate site of care of a patient with community-acquired pneumonia (CAP), especially whether hospitalisation is warranted or not, is one of the most important decisions in the overall emergency department management of such patients. It has consequences both with regard to the level of treatment received by the patient as well as the overall costs of treatment. Several tools have been developed to predict mortality and/or determine which patients could be sent home and treated safely with good clinical outcomes. The CRB-65 score is one of the validated severity of illness scoring tools recommended. This scoring system may be of particular benefit in resourceconstrained areas, as it is easier to use. Study’s aim: To determine whether it would be useful to introduce the CRB-65 severity of illness score in the routine evaluation of patients with CAP in the Helen Joseph Hospital Emergency Department (HJH ED). Study’s objectives: To determine what criteria HJH ED doctors use in their decision to admit or discharge CAP patients; to determine the frequency with which the CRB-65 severity of illness score is used in current practice by the HJH ED doctors for admitting or discharging CAP patients; and to determine the potential performance of the CRB-65 severity of illness score in the management of patients with CAP in the HJH ED. Design: Prospective, observational, hospital-based study.Patients and methods: All patients 18 years of age and older with the diagnosis of CAP constituted our study population. Data from 152 patients seen between February 2011 and April 2011 was collected and analysed. Outcome measures included hospital admission or discharge, time to clinical stability, length of hospital stay, and mortality. Results: Overall, 152 patients (79 females and 73 males) were included in the analysis. The median age was 36.5 years, with a range from 20 to 87 years. The chest radiograph was the commonest criterion (41%) used by the HJH ED doctors to determine the need for admission of the patients with CAP, while the haemodynamic parameters were the commonest criteria used (25.9%) for discharge decisions. On only three occasions was the CRB-65 score utilised out of the 193 criteria documented (1.55%). There was a significantly shorter time to clinical stability (p = 0.0069), but no tendency to a shorter length of hospital stay in patients with a lower CRB-65 score (p = 0.5694). Patients with a higher CRB-65 score were at significantly higher risk of death compared to patients with a lower CRB-65 score (p < 0.001). There were no deaths from outpatients, but there were a total of five deaths observed from the inhospital patients of which 3/5 patients (60%) would potentially have been classified as intermediate mortality risk and the remaining 2/5 patients (40%) as high mortality risk if the CRB-65 score had been the only criterion used as the standard for site of care decisions by the HJH ED doctors. Conclusion: The chest radiograph was the commonest criterion used by the HJH ED doctors to determine the need for admission of the patients with CAP, while the haemodynamic parameters were the commonest criteria used for discharge decision. The CRB-65 score is not frequently being used in current practice by the HJH ED doctors for admitting or discharging CAP patients. This study demonstrates the ability of the CRB-65 severity of illness score to accurately predict both the time to clinical stability for patients hospitalised with CAP and the risk of death associated. In addition, this study documents that the CRB-65 severity of illness score performed well in its ability to determine the initial site of care for patients with CAP. Setting: Emergency Department of the Helen Joseph Hospital.
Keywords: Pneumonia